The Evolving Impacts of the COVID-19 Pandemic on Gender Inequality in the U.S. Labor Market: The COVID Motherhood Penalty - Kenneth A. Couch; Robert W. Fairlie; Huanan Xu (Institute of Labor Economics (IZA), 2021)
We explore whether COVID-19 disproportionately affected women in the labor market using CPS data through the end of 2020. We find that male-female gaps in the employment-to-population ratio and hours worked for women with school-age children have widened but not for those with younger children. Triple-difference estimates are consistent with most of the reductions observed for women with school-age children being attributable to additional child care responsibilities (the "COVID motherhood penalty"). Conducting decompositions, we find women had a greater likelihood to telework, higher education levels and a less-impacted occupational distribution, which all contributed to lessening negative impacts relative to men.
Keywords: J16; J2; J13; 330; COVID-19; Coronavirus; pandemic; female labor supply; gender inequality; child care; motherhood penalty